Effect of Price Perception, Brand Trust, and Product Quality on Consumer Buying Behavior - Yuliastuti, Hilda (Journal Management & Economics Review (JUMPER), 2025)
This study examines the effect of price perception, brand trust, and product quality on consumer buying behavior. Using a quantitative approach with a sample of 150 respondents, data were analyzed through multiple regression to assess the individual and simultaneous influence of the three independent variables. The findings reveal that price perception, brand trust, and product quality each have a significant positive impact on consumer buying behavior, with all variables collectively explaining a substantial proportion of the variance in purchase decisions. These results highlight that consumers are more likely to engage in buying behavior when they perceive prices as fair, have trust in the brand, and evaluate the product as high quality. Theoretically, the findings align with the Stimulus-Organism-Response (S-O-R) framework, demonstrating that external factors such as price, trust, and quality act as stimuli shaping consumer evaluations and responses. Managerially, the study emphasizes the importance of integrating value-based pricing strategies, building and maintaining brand trust, and consistently delivering superior product quality to drive consumer purchasing decisions.